Bentuk Penyajian Musik Tari Burung Putih Oleh Grup Kesenian Talang Ojan Kabupaten Pali - Purnomo, Aji; Anton, Syahri (Jurnal Musik Etnik Nusantara, 2024)
The White Bird Dance is a story of farmers who are harvesting rice but are damaged by White Birds. The bird is a pest for farmers, especially rice farmers, because the bird damages the rice before the farmers harvest it, the music accompanying the dance is the Talang Ojan Arts Group, this group is a late generation group that currently still exists in Talang Ojan Village, Penukal Abab Lematang Ilir Regency, the music performed is poetic and has a Malay rhythm, with small gong instruments and drums as rhythm guides. The purpose of this research is to find out how the Form of Presentation of White Bird Dance Music by the Talang Ojan Arts Group of Pali Regency, with a subfocus on analyzing the form of dance music structure of White Bird Dance Music.The stages of data collection in this study include (1) Observation, (2) Interview, (3) Documentation. And the research data validity stage uses, and the stages of analyzing this research data include (1) Data Reduction, (2) Data Presentation, (3) Conclusion. From the research, the results found that each song in the White Bird Dance Music has a part of its structure, namely the existence of one melodic phrase with a repeating period, the question phrase from the vocal rhythm and the answer phrase from the violin, each of these structures is always repeated in the next section only the song text is different.